E-Service Quality dan Repurchase Intention pada Travel Agent Online di Wilayah DKI Jakarta - Sandriana Marina; Aswanti Setiawati; Nurun Ala Salehati (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
This research aims to identify the impact of e-service quality on repurchase intention of on-line travel agencies, especially in DKI Jakarta. On-line travel agency is a travel website (e-commerce) providing various services related to tourism, such as: on-line transportation and hotel bookings and entertainment. On-line travel agency also serves as an alternative option in addition to the conventional ones. This research employed quantitative approach. The data was gathered by distributing on-line questionnaire to 96 online travel agencies users as the samples. The data was then analyzed by using simple linear regression through SPSS 23. The result shows that e-service quality is in good category while repurchase intention is in very good category. The correlational value between e-service quality and repurchase intention is in the strong category and the percentage that shows e-service quality affects significantly positive to repurchase intention of 62,1% while 37,9% as the other variables not examined in this research.